The impact of elevated C-reactive protein level on the prognosis for oro-hypopharynx cancer patients treated with radiotherapy - Katano, Atsuto (Sci Rep, 2017)
The purpose of this study was to investigate an association between the prognosis for oro-hypopharynx squamous cell carcinoma treated with radiation therapy and the pre-therapeutic level of C-reactive protein (CRP). Patient with oro-hypopharyngeal squamous cell carcinoma who underwent definitive radiotherapy in our institution from January 2002 to August 2016 were enrolled. The patient were divided into elevated CRP (over 0.3 mg/dl) group and normal CRP groups, according to pre-treatment serum levels. There were 276 evaluable patients, and the median follow up was 41 months, ranging from 2 to 171 months. The 3-year OS and CSS for all enrolled patients were 67.0% and 72.8%, respectively. The OS and CSS rates were significantly worse in the elevated CRP group than in the normal CRP group, according to Kaplan-Meier survival curves analysed by a Log-rank test (p = 0.005 and p < 0.001, respectively). Multivariate analyses indicated that serum CRP levels remained independent predictors for both OS (HR: 1.588, p = 0.022) and CSS (HR: 1.989, p = 0.005). The pre-treatment CRP level is an independent predictor of treatment prognosis in patients with oro-hypopharyngeal cancer who underwent definitive radiotherapy. Especially, it is curious that an elevated CRP serum level is a significant predictor of loco-regional recurrence.